HUMAN DEVELOPMENT: HUMAN CAPITAL (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Human Capital is sum total of labour's capabilities, including skills, working capacity, education, health, and intelligence. Human Development is described as the process of enhancing human potential in terms of skills and rights.